2013
DOI: 10.1177/0333102413512032
|View full text |Cite
|
Sign up to set email alerts
|

Sphenopalatine ganglion neuromodulation in migraine: What is the rationale?

Abstract: Objective: The objective of this article is to review the prospect of treating migraine with sphenopalatine ganglion (SPG) neurostimulation. Background: Fuelled by preliminary studies showing a beneficial effect in cluster headache patients, the potential of treating migraine with neurostimulation has gained increasing interest within recent years, as current treatment strategies often fail to provide adequate relief from this debilitating headache.Common migraine symptoms include lacrimation, nasal congestion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 76 publications
1
54
1
3
Order By: Relevance
“…In a study by Ansari et al [53], 95% of patients with facial pain at the beginning of the study reported significant improvement after the study. The facial pain effect size observed in our study (d = 0.96) was much higher than that estimated from Young et al's data (d = 0.51), likely due to the application of multimodal frequencies (70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80) Hz and 1 MHz) in the AxioSonic system. Our effect size for quality of life measures using the SNOT-22 questionnaire (d = 0.45) was lower than Young et al's paper [40] (d = 0.9).…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…In a study by Ansari et al [53], 95% of patients with facial pain at the beginning of the study reported significant improvement after the study. The facial pain effect size observed in our study (d = 0.96) was much higher than that estimated from Young et al's data (d = 0.51), likely due to the application of multimodal frequencies (70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80) Hz and 1 MHz) in the AxioSonic system. Our effect size for quality of life measures using the SNOT-22 questionnaire (d = 0.45) was lower than Young et al's paper [40] (d = 0.9).…”
Section: Discussioncontrasting
confidence: 87%
“…The SPG is involved in tissue inflammation, lacrimation, mucus production and other parasympathetic processes [71][72][73][74]. Low frequency neurostimulation (20 Hz, much lower than ultrasound frequencies) of the SPG or the Vidian nerve leads to vasodilation and associated inflammation [75,76].…”
Section: Discussionmentioning
confidence: 99%
“…In theory, together with CGRP, peripheral VIP levels could contribute to objectively monitor migraine status and response to preventive treatments (27,28), which could be of specific help for a more objective follow-up of patients included in clinical trials, especially in those involving the cranial parasympathetic system, such as the stimulation of the sphenopalatine ganglion (29). As an example of this, both CGRP and VIP blood levels have been shown to be significantly higher in CM patients responding to onabotulinumtoxinA as compared to nonresponders (27).…”
Section: Discussionmentioning
confidence: 99%
“…42,44 Recent improvement in surgical technique and employment of of this therapy involves interruption of the postganglionic parasympathetic outflow and regulating the sensory inputs and processing in the nucleus caudalis of trigeminal. 39 Following the beneficial effect of this therapy in patients with cluster headache, this modality has gained interest in treating patients with migrainous headache. 39 However, the literature on SPG neuromodulation is mostly from small series of patients and needs to be validated by randomized clinical trials.…”
Section: A Peripheral Neuromodulationmentioning
confidence: 99%
“…39 Following the beneficial effect of this therapy in patients with cluster headache, this modality has gained interest in treating patients with migrainous headache. 39 However, the literature on SPG neuromodulation is mostly from small series of patients and needs to be validated by randomized clinical trials.…”
Section: A Peripheral Neuromodulationmentioning
confidence: 99%